Konstruksi Kepemimpinan Omar Bin Khattab:Analisis Representasi dan Retorika Politikdalam Serial Omar (2012) - Yuliyanda Aulia Sembiring; Siti Aliyah Balqis; Putri Adinda; Nursukma Suri (Kaganga:Jurnal Pendidikan Sejarah dan Riset Sosial Humaniora, 2026)
The purpose of this study is to determine the representation of Umar bin Khattab's leadership in the television series Omar (2012) as a construction of meaning in popular culture. The research method used is descriptive qualitative with multimodal analysis. Hall's approach is used to dissect the construction of leadership identity and ideology, supported by Teun A. Van Dijk's critical discourse analysis for verbal elements and Kress & van Leeuwen's social semiotics for visual elements. The results of the analysis show that this series reconstructs the values of justice ('adl) and deliberation (shūrā) not merely as historical facts, but as an ideological effort to present an alternative model of inclusive and accountable leadership amidst the modern political crisis. This study concludes that through eye-level camera angles and distinctive political rhetoric, audiovisual media successfully transforms classical Islamic narratives into political identities relevant to contemporary audiences. Keywords: Construction of Meaning, Islamic Leadership, Multimodal Analysis, Omar Series, Stuart Hall’s Representation.